THE PHENOMENON OF JOB HUGGING IN MILLENNIAL GENERATION EMPLOYEES: THE ROLE OF JOB INSECURITY AND TOXIC POSITIVITY IN CAREER STAGNATION - Supar Wasesa (Yayasan Multidimensi Kreatif, 2026)
Job hugging is an employment phenomenon that has been widely discussed recently, namely the tendency of employees to stay in their work positions passively, not because of satisfaction or affective commitment, but because of the fear of losing their job in the midst of a sluggish job market. This phenomenon is mostly found in millennial employees who started their careers in a period marked by repeated recessions, pandemics, and waves of layoffs in various sectors. This article aims to build a conceptual framework on the role of job insecurity and toxic positivity on job hogging tendencies, as well as how job hugging in turn contributes to career stagnation. Job insecurity is proposed as a predictor that encourages employees to restrain themselves in their work positions due to the perception of threats to job continuity, while toxic positivity, which is an organizational culture that demands excessive positive attitudes and suppresses reasonable expression of complaints, is proposed as the second predictor that makes employees reluctant to voice their dissatisfaction or seek career development opportunities openly. The study was compiled through a literature review on the theory of job insecurity, conservation of resources, toxic positivity, and career plateau, then formulated into a conceptual model along with five propositions involving job hugging as a mediator variable. This article makes a theoretical contribution in the form of expanding the understanding of the career plateau from the perspective of passive and hidden defensive behaviors, as well as practical implications for organizations in designing healthier work cultures and career development paths for millennial generation employees.